2011
DOI: 10.1111/j.1463-1318.2009.02165.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after surgery for rectal cancer with special reference to pelvic floor dysfunction

Abstract: Factors affecting QOL and pelvic floor function should be taken into account when making treatment decisions in rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 30 publications
1
34
1
1
Order By: Relevance
“…radiotherapy and sphincter-preserving surgery the longer-term consequences of treatment are emerging. In one prospective evaluation of rectal cancer patients, the results showed that while general QoL at 1 year was similar to pre-operative levels and psychological well-being was better, there was persistent anorectal dysfunction (Varpe et al, 2011). Indeed, in a study carried out by Schmidt et al (2005) patients who had sphincter preserving surgery (anterior resection) reported poorer quality of life as a consequence of impaired bowel function, in contrast to patients receiving an abdominoperineal resection (APR).…”
Section: Discussionmentioning
confidence: 96%
“…radiotherapy and sphincter-preserving surgery the longer-term consequences of treatment are emerging. In one prospective evaluation of rectal cancer patients, the results showed that while general QoL at 1 year was similar to pre-operative levels and psychological well-being was better, there was persistent anorectal dysfunction (Varpe et al, 2011). Indeed, in a study carried out by Schmidt et al (2005) patients who had sphincter preserving surgery (anterior resection) reported poorer quality of life as a consequence of impaired bowel function, in contrast to patients receiving an abdominoperineal resection (APR).…”
Section: Discussionmentioning
confidence: 96%
“…Using the validated SF-12 questionnaire, we found that quality of life in patients following rectal cancer resection was comparable with the general population. Varpe et al used the validated RAND 36-item health survey to assess quality of life after anterior and abdominoperineal resection [23]. The authors found no difference in general quality of life before and after operation, and mental functioning showed even better results postoperatively.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, sexual functioning in men was affected, often with permanent damage. 15 TAE, on the other hand, has a very low complication rate. Doornebosch et al 16 studied 50 patients, issuing them a quality of life survey before and after TAE.…”
Section: Pretreatment Differentiation (N=38)mentioning
confidence: 99%